2017
DOI: 10.1042/bcj20170129
|View full text |Cite
|
Sign up to set email alerts
|

Protein CoAlation: a redox-regulated protein modification by coenzyme A in mammalian cells

Abstract: Coenzyme A (CoA) is an obligatory cofactor in all branches of life. CoA and its derivatives are involved in major metabolic pathways, allosteric interactions and the regulation of gene expression. Abnormal biosynthesis and homeostasis of CoA and its derivatives have been associated with various human pathologies, including cancer, diabetes and neurodegeneration. Using an anti-CoA monoclonal antibody and mass spectrometry, we identified a wide range of cellular proteins which are modified by covalent attachment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
162
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 80 publications
(172 citation statements)
references
References 39 publications
8
162
0
2
Order By: Relevance
“…D clearly showed the characteristic peaks of CoA fragments from the precursor ion as indicated by the loss of 410, 428 and 508 Da (Fig. C,D), as has been observed in the recently reported publication . The peptide peaks of corresponding precursor ions minus CoA fragments (−409, −427 and −507 Da) were also abundant in the MS/MS spectrum.…”
Section: Resultssupporting
confidence: 83%
See 4 more Smart Citations
“…D clearly showed the characteristic peaks of CoA fragments from the precursor ion as indicated by the loss of 410, 428 and 508 Da (Fig. C,D), as has been observed in the recently reported publication . The peptide peaks of corresponding precursor ions minus CoA fragments (−409, −427 and −507 Da) were also abundant in the MS/MS spectrum.…”
Section: Resultssupporting
confidence: 83%
“…In our case, the treatment with CoASSCoA even at micromolar concentrations led to inactivation of CbGAPDH, whereas 10 mM GSSG, which is much higher than the physiological concentration, was required for complete inactivation of the enzyme. Consistently, it has been shown that the physiological concentration of GSSG is unlikely to lead to S-glutathionylation of GAPDH [6,33,34]. Although the significance of a CoASSCoAmediated mechanism in vivo remains unclear, accumulation of an intercellular concentration of CoASSCoA under oxidative stress would be a cause of CoAlation of CbGAPDH.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations